A smartphone-based three-in-one biosensor for co-detection of SARS-CoV-2 viral RNA, antigen and antibody. Issue 41 (4th May 2022) - Dou, Yanzhi; Su, Jing; Chen, Shixing; Li, Tie; Wang, Lihua; Ding, Xianting; Song, Shiping; Fan, Chunhai
Abstract : We report a universal and portable three-in-one biosensor linked to a smartphone for co-detection of SARS-CoV-2 viral RNA, antigen, and antibody. Abstract : Rapid and comprehensive diagnostic methods are necessary for early identification and monitoring of SARS-CoV-2. Here, we have developed a universal and portable three-in-one biosensor linked to a smartphone for co-detection of SARS-CoV-2 viral RNA, antigen, and antibody. In combination with a smartphone, the online monitoring of SARS-CoV-2 virus-infected patients from infection to immunization could be intelligently achieved.